Chimeric Osteocutaneous Free Flap Solution to Variation in Vascular Anatomy - Augustine J. Deering, III, BS; Payden A. Harrah, BS; Brian Wong Won, MD; John Michael Austin, BS; Mustafa T. Khan, DO; Jay K. Ferrell, MD; C. Anton Fries, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. When squamous cell carcinoma necessitates mandibular resection, the resultant defect can be complex. An osteocutaneous fibula free flap is an effective reconstruction option, typically supplied by the peroneal artery for both the fibula and skin flap. In this case report, an anatomical variation was found: the skin paddle was supplied by soleus musculocutaneous perforators of the posterior tibial artery, whereas the fibula was supplied by the peroneal artery. The posterior tibial artery perforator vessels from the skin paddle were anastomosed to the distal end of the peroneal vessels. The peroneal vessels were anastomosed to the left superior thyroid artery and a branch of the internal jugular vein, with confirmation of adequate blood flow via implantable Doppler signal. Septocutaneous perforators from the peroneal artery are absent in 5%–10% of the population; thus, an approach to anomalous vasculature in the setting of fibula free flap harvest that decreases morbidity and multiple operations is valuable.